Mycoflora associated with post-harvest disease of papaya (Carica papaya L.) and their pathogenic potentiality - Helal, Resuana Binte; Hosen, Sarowar; Shamsi, Shamim (Bangladesh Journal of Botany, 2018)
Nineteen species of fungi namely, Alternaria alternata (Fr.) Keissler, Aspergillus flavus Link, A. fumigatus Fresineus, A. niger Van. Tieghhm, Colletotrichum dematium (Pers.) ex. Fr., C. gloeosporioides (Penz.) Sacc., Corynespora citricola M.B. Ellis, Curvularia lunata Wakker, Fusarium flocciferum Corda, F. nivale (Fr.) Ces., Fusarium Link, Lasiodiplodia theobromae (Pat.) Griff & Moubl, Monilia Pers., Mucor Fresen, Penicillium Link, Pestalotiopsis guepinii (Desm.) Stay., Rhizoctonia solani J.G. Kuhn, Rhizopus stolonifer Bull. and Syncephalastrum Schroet were found to be associated with the diseased fruits of Carica papaya L. Among the isolated fungi C. gloeosporioides, F. nivale and Fusarium sp. were found to be pathogenic for both red and yellow cultivar Shahi papaya. Association of C. lunata, F. nivale, P. guepinii and Syncephalastrum sp. with papaya is a new record. The present report is the first record of Corynespora citricola and Fusarium flocciferum from Bangladesh.